TWEAK and Fn14 in the Neurovascular Unit - Yepes, Manuel (Frontiers in Immunology, 2013)
The neurovascular unit (NVU) is a dynamic structure assembled by endothelial cells, a basement membrane, perivascular astrocytes, pericytes, and surrounding neurons. The NVU regulates the passage of substances and cellular elements from the intravascular space into the brain parenchyma. This function, also known as blood-brain barrier (BBB), is regulated by the integrity of tight junctions proteins between endothelial cells, and the interaction between perivascular astrocytes and the basal lamina. The cytokine tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and its receptor fibroblast growth factor-inducible 14 (Fn14) are abundantly expressed in the NVU. Here we will review data indicating that the interaction between TWEAK and Fn14 in the endothelial cell - basement membrane - astrocyte interface regulates the function of the BBB following an ischemic/hypoxic injury, and that pharmacological inhibition of TWEAK-Fn14 is a promising target for the treatment of patients with neurological diseases that have a direct impact on the structure and function of the NVU.